Palliative Care for the Interstitial Lung Disease Patient a Must and Not Just a Need. (June 2022) - Chaaban, Said; McCormick, James; Gleason, Debra; McFarlin, Jessica M.
Patients with interstitial lung disease (ILD) have many unmet palliative care needs. The majority of patients with chronic ILD have poor access to a specialist in palliative medicine and that is due to several barriers. The mortality for the ILD patient is high and reaches up to 80% if admitted to the ICU with respiratory failure. Palliative care addresses symptoms in diseases where cure is unlikely or impossible. Palliative care consultation also ensures communication among patients, caregivers and providers regarding treatments, prognosis, and end of life planning.Methods: We performed a literature review on palliative care and ILD, accessing articles published since 2002. We found 71 articles related to the topic. We chose 37 that were most relevant and with no redundancy of information to include in this review. Objectives: Summarize the palliative care needs of patients with ILD, discuss the barriers to receiving palliative care, and summarize clinical practice for providing palliative care to this patient population.